Radiographic change is common in new presenters in primary care with hip pain. PCR Hip Study Group. - Birrell, F; Croft, P; Cooper, C; Hosie, G; Macfarlane, G; Silman, A (2000)
To determine the prevalence of radiographic osteoarthritis in subjects with hip pain newly presenting to primary care.